Biomechanical study of total disc replacement prosthesis on spinal facet joint using finite element method - Suarin, Mohd Azizan (2021)
Low back pain (LBP) is a pain or muscle tension that happens at the lumbar region that could lead to disability and work absenteeism which cause increasing health care cost and socioeconomic burden. The causes of LBP include degenerative of intervertebral disc and facet joint osteoarthritis. Total disc replacement (TDR) was introduced to reduce pain and preserve segmental motion of the cervical and lumbar spine caused by LBP. The development of lumbar prosthesis is still evolving, as the effectiveness of this approach are not as reliable as hoped. Furthermore, the biomechanical effects of body weight on implanted lumbar spine after TDR are yet to be fully understood particularly at facet joint. Thus, the aim of this study was to investigate the biomechanical effects after TDR towards human body weight on the range of motion (ROM) and facet joint stress at the treated level as well as adjacent segments of the implanted lumbar spine. Three dimensional finite element model of the osseoligamentous lumbar spine and implanted lumbar spine models with Prodisc-L® was developed and verified with previous studies. The finite element model was subjected to 8 Nm moment for flexion, 6 Nm moment for extension, 6 Nm moment for lateral bending and 4 Nm moment for clockwise rotation of the spine motions. These load conditions for each motion was combined with follower compression load of 650 N for normal, 750 N for overweight and 850 N for obese human weight. It was observed that implanted spine with Prodisc-L® has increased the ROM during the flexion-extension and lateral bending motions. However, the ROM was decreased 7% in axial rotation motion due to the rigidity and design of the prosthesis. At the treated level of L4L5, the facet stress values increased from 12% to 27% after Prodisc-L® implantation. This is due to the constraint of the anterior longitudinal ligament which transmitted from the adjacent level of implanted to the treated level during lumbar spine motions. However, an opposite trend was shown as the human weight increased from normal to obese, where the ROM of the implanted lumbar spine decreased in all spine motions in a ranged from 0.6% to 13%. This phenomenon was due to the applied compressive follower load that was subjected as human weight. Meanwhile, a significant facet stress was generated in most of the lumbar spine motions as human weight increased from normal to obese, whereas higher facet stresses were generated in rotational motion and flexion motion. The highest increasing trend of 85% was found in the treated level of L4L5 of the right facet. This phenomenon was caused by the increasing compressive follower load that leads to the change in the positions of superior and inferior facet. Thus, the combination of lack of stiffness, the rigidity of the prosthesis and obesity may speed up the progression rate of facet degeneration that could lead to reoccurrence of LBP. These findings will provides useful data to assist both surgeons and engineers with problems related to patients’ facet joint after TDR mostly among obese patients.